Determinants of the Success of Zakat Utilization in Alleviating Poverty - Candri Candri; Abdul Aziz; Sri Rokhlinasari; Abdul Rohman (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Zakat has increasingly been recognized as a strategic Islamic economic instrument for poverty alleviation and social welfare development. However, the effectiveness of zakat in improving the economic conditions of mustahik remains inconsistent due to complex interactions among institutional, psychological, and economic factors. Despite extensive studies on zakat distribution and poverty reduction, few have examined the structural relationships among these factors using a comprehensive quantitative approach. Therefore, this study aims to analyze the determinants of successful zakat utilization in alleviating poverty. This study employs a quantitative approach using Structural Equation Modeling (SEM) to examine the relationships among key variables influencing zakat program effectiveness. The sample consists of 258 mustahik who participated in productive zakat programs in West Java, Indonesia. Data were collected via structured questionnaires using a five-point Likert scale and analyzed with AMOS. The results indicate that the proposed model demonstrates an acceptable level of goodness-of-fit, with values of CMIN/DF = 2.551, CFI = 0.902, TLI = 0.887, and RMSEA = 0.078. The findings reveal that organizational support significantly influences education, motivation, entrepreneurship, and economic empowerment, while education and motivation significantly contribute to economic empowerment. Furthermore, economic empowerment directly contributes to poverty alleviation, suggesting that productive zakat programs can generate sustainable welfare improvements when supported by robust institutional mechanisms. These findings suggest that zakat institutions should strengthen capacity-building programs, entrepreneurial mentoring, and integrated empowerment strategies to enhance the long-term effectiveness of zakat in alleviating poverty.